Motions in liquid-vapour interfaces by using a continuous mechanical model - Henri Gouin (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2013)
By using a limit analysis for the motion equations of viscous fluid endowed with internal capillarity, we are able to propose a dynamical expression for the surface tension of moving liquid- vapour interfaces without any phenomenological assumption. The proposed relation extends the static case, yields the Laplace formula in cases of mass transfer across interfacial layers and allows to take the second coefficient of viscosity of compressible fluids into account. We generalize the Maxwell rule in dynamics and directly explain the Marangoni effect.